2014
DOI: 10.11113/jt.v69.3172
|View full text |Cite
|
Sign up to set email alerts
|

Potential Source and Extraction of Vitamin E From Palm-Based Oils: A Review

Abstract: Vitamin E is essential in the human body which naturally found in vegetable fats and oil and their derived products. Several palm-based oils obtained from palm oil mills and refineries were revised in this paper as the raw material for vitamin E. Tocopherols and tocotrienols isomers of the vitamin E content are found nearly comparable with crude palm oil. To obtain the tocopherols and tocotrienols, various developed technologies for the extraction were also reviewed. These include the solvent-based extraction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…However, the thermal stability of the tocopherols is essentially low and decomposition occurs easily during molecular distillation. Therefore, their recovery ratio is not high and is around 50% (Jiang et al, 2006;Maarasyid et al, 2014). Additionally, impurities such as sterols cannot be completely removed from the tocopherol-rich fraction Martins, Ito, Batistella, & Wolf-Maciel, 2006;Nagao et al, 2005;Ooi, Choo, Yap, Basiron, & Ong, 1994;Ramamurthi & McCurdy, 1993).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, the thermal stability of the tocopherols is essentially low and decomposition occurs easily during molecular distillation. Therefore, their recovery ratio is not high and is around 50% (Jiang et al, 2006;Maarasyid et al, 2014). Additionally, impurities such as sterols cannot be completely removed from the tocopherol-rich fraction Martins, Ito, Batistella, & Wolf-Maciel, 2006;Nagao et al, 2005;Ooi, Choo, Yap, Basiron, & Ong, 1994;Ramamurthi & McCurdy, 1993).…”
Section: Introductionmentioning
confidence: 96%
“…Tocopherols are found only in vegetable oils such as soybean oil, rapeseed oil, and sunflower oil in very low concentrations of about 0.1-0.5 wt% (Carpenter, 1979;Desai, Bhagavan, Salkeld, & Dutra de Oliveira, 1988;Ferrari, Schulte, Esteves, Brühl, & Mukherjee, 1996;Herting & Drury, 1963;Verleyen et al, 2002). To recover these tocopherols, molecular distillation is commercially used as a separation process (Jiang, Shao, Pan, & Zhao, 2006;Maarasyid, Muhamad, & Supriyanto, 2014;Martins, Batistella, Maciel-Filho, & Wolf-Maciel, 2006). The deodorizer distillate is a by-product of edible oil refining and its vitamin E concentration is 40 times higher than that of the crude oils (Ferrari et al, 1996;Verleyen et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been shown that tocotrienols and tocopherols constitute 70% and 30% of total vitamin E, respectively, in palm oil. The average total content of vitamin E in the commercial variety of crude palm oil was found to be 600 parts per million (ppm) (12); palm oil is considered to be the best source of tocotrienols (13). The predominant isomer found in plant seeds is g-tocopherol, while a-tocopherol is mainly present in leaves.…”
mentioning
confidence: 99%